2020
DOI: 10.4108/eai.11-11-2020.166958
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Correlated Renal Fault Prediction through Deep Learning

Abstract: INTRODUCTION: Diabetic nephropathy is one of the complications of diabetes that causes damage to kidneys. Deep learning techniques are widely used to predict different diseases. OBJECTIVES: The main aim of this work is to develop an effective prediction model using deep learning. To get an effective model, a suitable dataset is considered that comprises of features related to diabetic nephropathy. METHODS: Deep belief network (DBN) is the proposed deep learning technique which is compared with naive bayes, CAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 18 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…While kNN with principal component analysis (PCA) had the maximum sensitivity, it had a low specificity, suggesting that the classifier was less accurate than kNN. S.S. Reddy et al [16] have worked on diabetes mellitus (DM) patients and their correlated ailments [17] like renal fault [18]. Through this research, they have identified that people's stress may affect DM.…”
Section: Related Workmentioning
confidence: 99%
“…While kNN with principal component analysis (PCA) had the maximum sensitivity, it had a low specificity, suggesting that the classifier was less accurate than kNN. S.S. Reddy et al [16] have worked on diabetes mellitus (DM) patients and their correlated ailments [17] like renal fault [18]. Through this research, they have identified that people's stress may affect DM.…”
Section: Related Workmentioning
confidence: 99%